Roles of Macrophage Polarization and Macrophage-Derived miRNAs in Pulmonary Fibrosis - Kishore, Amit; Petrek, Martin (Frontiers in Immunology, 2021)
This mini-review summarizes current evidence for the role of macrophage activation and polarization in inflammation and immune response pertinent to interstitial lung disease, specifically pulmonary fibrosis. In the fibrosing lung, production and function of inflammatory and fibrogenic mediators involved in the disease development has been reported to be regulated by effects of polarized M1/M2 macrophage populations. The M1 and M2 macrophage phenotypes were suggested to correspond with the pro-inflammatory and pro-fibrogenic signatures, respectively. These responses towards tissue injury followed by the development and progression of lung fibrosis are further regulated by macrophage-derived microRNAs (miRNAs). Besides cellular miRNAs, extracellular exosomal-miRNAs derived from M2 macrophages have also been proposed to promote the progression of pulmonary fibrosis. In future perspective, harnessing the noncoding miRNAs with key role in the macrophage polarization is, therefore, suggested as promising therapeutic strategy for this debilitating disease.